Epic [videorecording (DVD)] - Beyoncé, 1981-; Farrell, Colin, 1976-; Seyfried, Amanda (Twentieth Century Fox Home Entertainment, 2013)
The story of an ongoing battle deep in the forest between the forces of good and the forces of evil. When a teen age girl finds herself magically transported into this secret universe, she must band together with a rag-tag team of fun and whimsical characters in order to save their world, and also ours.